1983
DOI: 10.1021/bi00288a010
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement of subunit IV in beef heart cytochrome c oxidase probed by chemical labeling and protease digestion experiments

Abstract: The arrangement of subunit IV in beef heart cytochrome c oxidase has been explored by chemical labeling and protease digestion studies. This subunit has been purified from four samples of cytochrome c oxidase that had been reacted with N-(4-azido-2-nitrophenyl)-2-aminoethyl[35S]-sulfonate (NAP-taurine), diazobenzene[35S]sulfonate, 1-myristoyl-2-[12-[(4-azido-2-nitrophenyl)amino]lauroyl]-sn-glycero-3- [14C]phosphocholine (I), and 1-palmitoyl-2-(2-azido-4-nitrobenzoyl)-sn-glycero-3-[3H]phosphocholine (II), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Therefore, it would seem that the inhibition of labeling obtained with DTT might be a result of its partitioning within the bilayer since DTT is freely soluble in a variety of organic solvents whereas glutathione is not. These observations are further supported by the results of Malatesta et al (1983), who have shown that similarly labeled phosphatidylcholine selectively labels cytochrome c oxidase in its hydrophobic membrane-spanning stretch.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, it would seem that the inhibition of labeling obtained with DTT might be a result of its partitioning within the bilayer since DTT is freely soluble in a variety of organic solvents whereas glutathione is not. These observations are further supported by the results of Malatesta et al (1983), who have shown that similarly labeled phosphatidylcholine selectively labels cytochrome c oxidase in its hydrophobic membrane-spanning stretch.…”
Section: Discussionsupporting
confidence: 74%
“…Finally, there is the problem of what the length of a transmembrane helix actually is. We find that 18or 19-residue segments are more useful in locating the probable transmembrane stretches in a membrane protein than longer segments if hydrophobicity profiles are used because charged residues may be present particularly in the lipid head region (3,6,7,15). The transmembrane helices observed in the crystal structure of the photosyn-thetic reaction center of Rhodopseudomonas viridis range in length from 24-30 residues and, therefore, can not be predicted in their entirety from the hydrophobicity profile of a 19-residue moving window using the hydropathy scale of Kyte and Doolittle (5,19) or Table I (3).…”
Section: Resultsmentioning
confidence: 98%
“…Hydrophobicity sums were obtained for a moving window of 19-residue segments using an adapted computer program from Kyte and Doolittle (5). The transmembrane helices predicted using this scale correspond to the lipid-buried segments of the two transmembrane helices in subunit II and the single transmembrane helix in subunit IV of beef heart COX located by the arylazidophospholipid labeling experiments of Buse et al (6,7).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously used trypsin cleavage, as well as chemical labeling with 3Hand uC-labeled arylazidophospholipids, [3H]-(V-(4-azido-2-nitrophenyl)-2-aminoethanesulfonate and [35S]diazobenzenesulfonate, to examine the topology of C(v in beef heart cytochrome c oxidase (Malatesta et al, 1983). We concluded that this polypeptide was oriented with its N-terminus on the M side and its C-terminus on the C side of the inner membrane, but with the C-terminus mostly buried by protein-protein interactions.…”
Section: Resultsmentioning
confidence: 99%